Mendeley-Based Training to Improve Reference Management and Citation Formatting in Sociology Students - Puspita Rizki, Dian; Soulthoni, Hannin Pradita Nur (Lembaga Riset dan Inovasi Masyarakat Madani, 2025)
This program was conducted at the Department of Sociology, Faculty of Social and Political Sciences, Halu Oleo University, to address challenges in scientific writing, particularly in reference management, academic ethics, and citation formatting. Students often struggled with these issues, hindering their ability to write quality academic papers. The program aimed to equip students with skills to organize references, compile bibliographies, and apply citation formats using Mendeley. The program’s success was reflected in a 40% improvement in reference management skills, a 45% increase in Mendeley usage, and a 35% improvement in understanding academic ethics. Additionally, students’ ability to correctly format citations and compile bibliographies improved by 45%. Final-year students showed substantial progress, enhancing their academic writing capabilities. These results highlight the importance of integrating Mendeley training into the curriculum, and it is recommended that such training be regularly incorporated into research methodology courses to foster long-term academic success.